2012
DOI: 10.1038/sc.2012.99
|View full text |Cite
|
Sign up to set email alerts
|

Study on the safe range of shortening of the spinal cord in canine models

Abstract: Study design: Experimental dog model of spinal cord shortening. Objectives: To clarify the relationship between the amount of shortening of the spinal cord and the degree of injury it may induce, and to determine the safe range of the shortening. Setting: Xi'an Jiaotong University, China. Methods: Thirty adult dogs were randomly allocated to five groups. Dogs in Group A (sham operation control) underwent spondylectomy to have two-thirds of the thirteenth thoracic segment (T13) resected, without bone-to-bone co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…For non-deformity spinal column, Kawahara and other researchers also indicated that a proper spinal column shortening could not injure the spinal cord and could increase the SCBF in animal experiment. [ 19 , 20 ] In this study, the SCBF could maintain at a satisfaction level to avoid SCI and proved its protection effect of blood flow, although the SCBF did not continued to increase during repeated shortening. The reason is that the correction operation might be harmful to the SCBF and it partially counteracted the benefit of the shortening.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…For non-deformity spinal column, Kawahara and other researchers also indicated that a proper spinal column shortening could not injure the spinal cord and could increase the SCBF in animal experiment. [ 19 , 20 ] In this study, the SCBF could maintain at a satisfaction level to avoid SCI and proved its protection effect of blood flow, although the SCBF did not continued to increase during repeated shortening. The reason is that the correction operation might be harmful to the SCBF and it partially counteracted the benefit of the shortening.…”
Section: Discussionmentioning
confidence: 59%
“…The author also found that more than 2/3 vertebral segment height shortening can cause an irreversible SCI. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Some animal studies reported that SCI occurred from a spinal shortening of more than one-half to two-thirds 10,15,17) or 73.8% of the vertebral body height (VBH) 25) . However, a clinical study by Bourghli et al 3) reported that 10 patients treated with modified closing-opening wedge osteotomy at the TL junction and underwent shortening of the VBH by 35% and 38% showed transient neurological deficits postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques use posterior spinal shortening as a basic mechanism for a large correction angle. Therefore, over-shorting and redundancy of spinal cord are likely to occur, resulting in neurological deficits 3,15) .…”
Section: Introductionmentioning
confidence: 99%
“…Proper range of spinal shortening brings about vasodilation of the arteries of the spinal cord, which could result in the concomitant reduction of resistance to blood flow and increase the diameter of the anterior spinal artery by 138% compared to base line. Moreover, SCBF could be increased by 111%-160% compared to the base line before shortening [ 19 , 23 , 25 ]. Based on the abovementioned studies, the spinal shortening could reduce the spinal tension and increase SCBF, which are critical for the neurological recovery in sSCI.…”
Section: Discussionmentioning
confidence: 99%